2012
DOI: 10.1111/j.1741-3729.2011.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Relationship Help Seeking Prior to a Marriage Checkup

Abstract: Although the barriers to couples’ help seeking can be daunting, to date there is only a small body of literature addressing the factors that motivate couples to seek help. This study examined the association between attitudes towards relationship help seeking and relationship help seeking behaviors, as well as the association between marital quality and help seeking. This study was completed in the context of the Marriage Checkup, a brief intervention designed to reduce the barriers to help seeking. Results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 38 publications
1
16
1
Order By: Relevance
“…This confirms past research on gender differences in relationship satisfaction and depression (Beach & Whisman, ). This finding may help to explain consistent research that suggests women are more likely to seek counseling than their male partners (Eubanks Fleming & Córdova, ), as they may be more attuned to and effected by relationship problems (Shill & Lumley, ).…”
Section: Discussionmentioning
confidence: 53%
“…This confirms past research on gender differences in relationship satisfaction and depression (Beach & Whisman, ). This finding may help to explain consistent research that suggests women are more likely to seek counseling than their male partners (Eubanks Fleming & Córdova, ), as they may be more attuned to and effected by relationship problems (Shill & Lumley, ).…”
Section: Discussionmentioning
confidence: 53%
“…Results from the present study indicated that females reported more presenting issues than men and were more likely to indicate '[their] partner's behavior' as a problem. It is important to acknowledge that males are less likely to initiate relationship counseling than females (Fleming & Córdova, 2012) and hence, it may be appropriate to suggest that the partner who initiates couples counseling is more likely to express a greater number of presenting issues by comparison.…”
Section: Presenting Issuesmentioning
confidence: 99%
“…Within the TPB framework, low relationship satisfaction has been associated with positive subjective norms but not with attitudes (Spiker et al, 2019). These associations are also expected in women, as relationship satisfaction plays an important role in women’s decisions to seek help (Eubanks-Fleming & Cordova, 2012). One untested possibility is that relationship satisfaction has a positive association with PBC.…”
Section: Tpb and Couple Help Seekingmentioning
confidence: 92%
“…Individuals low in relationship satisfaction (i.e., subjective evaluation of a romantic relationship; Funk & Rogge, 2007) are more likely to seek couple therapy (Eubanks-Fleming & Cordova, 2012). Within the TPB framework, low relationship satisfaction has been associated with positive subjective norms but not with attitudes (Spiker et al, 2019).…”
Section: Tpb and Couple Help Seekingmentioning
confidence: 99%